Development of monopoly learning media in lactation education classes - Hapitria, Pepi; Nurlina, Neli (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2024)
Background: Exclusive breastfeeding is one of the rights that children should have, as breastfeeding for the first six months is the best way to fulfill a child's nutritional needs to continue the growth of their brain, liver, and immune system. Exclusive breastfeeding can also reduce infectious mortality by 88 percent in infants less than 3 months old. Currently, the achievement of exclusive breastfeeding is 69.7% and has met the 2021 target of 45%. One of the causes is influenced by the learning process. Interesting and fun learning media can affect learning outcomes. Therefore, it is important for midwives to grow the interest and attractiveness of pregnant women in the learning process with the help of appropriate learning media and involve pregnant women in lactation education classes through Monopoly games. Objectives: This study aims to develop Monopoly game media in lactation education classes and describe the feasibility of Monopoly game media as learning media in lactation education classes for pregnant women. Methods: This study uses research and development methods, namely expert sampling. The data collection instrument was a Likert scale questionnaire and descriptive statistical analysis techniques. The design of research activities only reached the feasibility test of monopoly learning media. Results: The learning media developed regarding the feasibility of learning aspects by material experts and users obtained an average score of 4.32, entered the good category. Meanwhile, according to media experts, an average score of 4.9 was obtained based on media engineering aspects, and based on visual communication aspects, an average score of 4.62 was obtained. Conclusions: This study shows that the development media for lactation education classes in the form of monopoly is in a good category and suitable for use